2005
DOI: 10.1111/j.1460-9568.2004.03860.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of spontaneous mouth/tongue movement and related neural activity, and their repression in fetal mice lacking glutamate decarboxylase 67

Abstract: Spontaneous body movement starts at early fetal stage, at embryonic day (E) 12-15 in mice. In the present study, the movement of the head region was studied in E13-14 mice by in utero ultrasound imaging, together with the in vitro recording of underlying neural activities in the hypoglossal nerve and the ventral root of the upper cervical cord of an isolated brainstem-spinal cord preparation. The role of gamma-aminobutyric acid (GABA) in the generation of fetal movement was assessed using mice lacking GABA-syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Therefore, it likely represents a nonrespiratory activity. This is consistent with previous works obtained in rat ) and mice (Tsunekawa et al, 2005) combining recordings of C4 activity with either the diaphragm or the hypoglossal nerve activities and describing at early developmental stages generation of low-frequency discharges not related to respiratory activity.…”
Section: Lf Activity Is a Primordial Activitysupporting
confidence: 81%
“…Therefore, it likely represents a nonrespiratory activity. This is consistent with previous works obtained in rat ) and mice (Tsunekawa et al, 2005) combining recordings of C4 activity with either the diaphragm or the hypoglossal nerve activities and describing at early developmental stages generation of low-frequency discharges not related to respiratory activity.…”
Section: Lf Activity Is a Primordial Activitysupporting
confidence: 81%
“…It is not in line with the finding of reduced GAD67 expression in the cerebellum of patients with mood disorders [33]. GAD67 knockout animals do not show an affective phenotype [68]. In contrast, affective correlates have been described in GAD65-knockouts, for example altered conditioned fear behaviour [41], increased anxietylike behaviour in a light/dark avoidance test, reduced aggression between male animals, reduced forced-swimming-induced immobility [42], increased anxiety in the open field and the elevated zero maze [43].…”
Section: Discussionmentioning
confidence: 63%
“…Oscillations intermingled with nonoscillatory bursts also resemble the pattern of electrical discharges detected from the mouse spinal cord at E14.5 (Yvert et al, 2004). In experiments using rat and mouse embryos in vivo and in utero (Suzue & Shinoda, 1999;Tsunekawa et al, 2005) and in human fetuses (de Vries et al, 1982), spontaneous body movement has been observed and is considered to be related to the spontaneous electrical discharges recorded in vitro. To further exclude the possibility that the spontaneous activity simply appeared when the tissue was stained, we compared electrical discharges in unstained and stained preparations.…”
Section: Detection Of the Spontaneous Wave Of Activitymentioning
confidence: 81%